Pengaruh Return on Equity (ROE), Net Profit Margin (NPM) Dan Return on Assets (ROA) Terhadap Harga Saham yang Terdaftar dalam Indeks Emiten LQ45 Periode 2019-2021 - Riyan Hariyadi; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine and analyze the simultaneous and partial effect of Return On Equity (ROE), Net Profit Margin (NPM) and Return On Assets (ROA) from the stock costs of organizations remembered for the LQ45 Record during the 2019-2021 period. The location of this study can be viewed on the Indonesian Stock Exchange (idx.co.id) website. This is a quantitative study where data is obtained by downloading data from the financial reports of companies in the LQ45 index for the 2019-2021 period. The sampling technique in this study used purposed sampling technique with certain considerations. Based on these criteria, the number of issuers is 29. Data were analyzed using various linear regression tests, autocorrelation tests and determination tests. Given the consequences of examining the information, the consequences of the F test show the same time Return On Equity, Net Profit Margin and Return On Assets affect stock costs in organizations recorded in the LQ45 list for the 2019 - 2021 period. Furthermore, the results of the t test show that Return On Equity (ROE) has a significant positive effect on stock prices in companies listed in the LQ45 index for the 2019 – 2021 period. Net Profit Margin (NPM) and Return On Assets (ROA) have no significant positive effect on stock prices in companies listed in the LQ45 index 2019 – 2021 period. The score of the determination test show that the percentage is 68.7%, where share prices can be influenced by Return On Equity, Net Profit Margin and Return On Assets. For investors, it is better if before investing in an investor company, examine further related to the financial situation of a company so that the company will not be disadvantaged even if the company can’t achieve the return on investment that investors expect .Keywords: Stock price, return on equity (ROE), net profit margin (NPM) and return on assets (ROA).